Application of optimal band-limited control protocols to quantum noise sensing - V. M. Frey (Nature Portfolio, 2017)
Control of qubits’ frequency response by dynamical decoupling is usually vexed by control’s out-of-band harmonics, a problem known in metrology as “spectral leakage”. Here, the authors reduce this problem by orders of magnitude exploiting discrete prolate spheroidal sequences to control a trapped-ion qubit.